Enhanced Peat Profiling with Electrical Resistivity Tomography and Multichannel Analysis of Surface Wave - Alsidqi, Hasan; Jeffery Guan Kiat, Tay; Lin Jye, Lee (Springer Nature, 2024)
Infrastructure development into peat necessitates geotechnical engineers to find a better profiling method. The conventional profiling carried out by either a localized peat augering or a borehole drilling is often subjective, lacking of details, time consuming and high cost. This paper presents results and analysis of in-situ tests that combines Electrical Resistivity Tomography (ERT) and Multichannel Analysis of Surface Wave (MASW) methods. The results show that ERT method is a good tool for delineating the boundary between peat and underlying mineral soil using their large contrast in electrical resistivity values. The ERT enables the peat thickness to be determined accurately, but lacks of information regarding peat mechanical properties. On the other hand, the MASW provides a lower contrast between the peat and the mineral soil layers compared to the ERT, but it can provide the mechanical properties of the two layers based on shear wave velocity measurements. Hence, the combination of these two methods were found to be improving the peat profiling for engineering application. The results correlate well with the existing peat auger and borehole records in the study area. The combined ERT and MASW methods is recommended to be practically used by engineers as the current best solution for peat profiling.